The Impact of Financial Risk on Insurance Company Performance with Hedge Accounting as a Moderating Variable - Didin Supyanudin; Sudjono (Indonesian Journal of Business Analytics, 2024)
The public's confidence in insurance companies has been damaged by state-owned insurance companies' inability to pay claims. The purpose of this research is to investigate how financial risk affects business performance and how hedge accounting mitigates that influence. This study uses a quantitative approach. The analysis makes use of secondary data from 2019 to 2022 from insurance firms' annual reports. Both moderated regression analysis (MRA) and multiple linear regression analysis are used in this investigation. The findings show that return on assets (ROA) is significantly and negatively impacted by credit risk. Return on assets is unaffected by market, insurance, liquidity, and operational risks. The MRA analysis demonstrates how hedge accounting can increase the impact of risk associated with credit and insurance returns on assets. Hedge accounting, however, has no effect on how much market, operational, and liquidity risk affect return on assets.